An unexpected, mild phenotype of glucocorticoid resistance associated with glucocorticoid receptor gene mutation case report and review of the literature - Ágnes Molnár; Attila Patócs; István Likó; Gábor Nyírő; Károly Rácz; Miklós Tóth; Beatrix Sármán (BMC, 2018)
Abstract Background Glucocorticoid resistance is a rare, sporadic or familial condition caused by mutation of the gene encoding the glucocorticoid receptor (GR). Clinically it is characterized by symptoms developed due to local, tissue-specific, or generalized partial insensitivity to glucocorticoids. Case presentation A 31-year-old woman was evaluated because of infertility at the Endocrine Unit of the 2nd Department of Medicine, Semmelweis University. During her laboratory investigations, elevated serum and salivary cortisol were observed which failed to be suppressed after administration of 1 mg dexamethasone. 24 h urinary cortisol was increased, but a normal midnight serum cortisol was detected suggesting a maintained circadian rhythm. Plasma dehydroepiandrosterone-sulfate and androstendione levels were also elevated. Repeated plasma ACTH measurements indicated slightly elevated or normal values. Bone mineral density was normal. All laboratory results confirmed the diagnosis of glucocorticoid resistance. Genetic counseling followed by Sanger sequencing of the coding region of the gene encoding human glucocorticoid receptor was performed and a missense mutation (Arg714Gln, R714Q) in a heterozygous form was detected. Following family screening, the same mutation was found in her clinically-healthy 35-year-old sister who had no fertility problems.This variant was not detected in more than 60 patients and controls tested either for glucocorticoid resistance or Cushing's syndrome in our Laboratory and it was absent in Exome Variant Server, HumanGene Mutation Database and ExAC databases. Conclusions Our case fulfils the diagnostic criteria of glucocorticoid resistance, also named Chrousos syndrome. The glucocorticoid receptor gene mutation detected in our patient has been already reported in a 2-year-old child with hypoglycaemia, hypokalaemia, hypertension and premature puberty. These distinct phenotypes may suggest that other factors may modify the functional consequences of the R714Q variant of GR.